Respuesta :
Answer:
factor:
x^2+2x+2x+4
x(x+2)+2(x+2)
(x+2)(x+2)
100x^2+20x+1
100x^2+10x+(10x+1)
10(10x+1)+(10x+1)
(10x+1)(10x+1)=(x+2)(x+2)
Hope this helps you
Answer:
1/9, (-3)/11
Step-by-step explanation:
Both the left and right side are perfect squares,
(x + 2)^2 = (10x + 1)^2
In order for the squares to be equal, we must have the inner expressions equal to each other or negations of each other:
(x + 2) = [tex]\pm[/tex] (10x + 1)
or
x + 2 = -10x - 1
Simplifying the first equation gives 9x = 1 so 1/9 and simplifying the second equation gives 11x = -3, so (-3)/11